2004
DOI: 10.1038/sj.mp.4001497
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphism in ethanol metabolism: acetaldehyde contribution to alcohol abuse and alcoholism

Abstract: Acetaldehyde, the first product of ethanol metabolism, has been speculated to be involved in many pharmacological and behavioral effects of ethanol. In particular, acetaldehyde has been suggested to contribute to alcohol abuse and alcoholism. In the present paper, we review current data on the role of acetaldehyde and ethanol metabolism in alcohol consumption and abuse. Ethanol metabolism involves several enzymes. Whereas alcohol dehydrogenase metabolizes the bulk of ethanol within the liver, other enzymes, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
96
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(100 citation statements)
references
References 175 publications
(229 reference statements)
1
96
0
Order By: Relevance
“…The ALDH2*2 allele is common in East Asian populations, in whom it has a well-established protective effect associated with about a 10-fold reduction in risk of alcoholism. 82 The protective effect is thought to be a direct consequence of the flushing reaction and associated nausea, drowsiness and headache that discourages drinking. In a recent meta-analysis, 83 researchers found clear evidence of a correlation between ALDH2 genotype and alcohol exposure (alcohol exposure being considered an environmental risk factor for cancer in much the same way that some psychiatrists view cannabis use as an environmental risk factor for schizophrenia).…”
Section: Genotype-environment Associations: Challenges In Identifyingmentioning
confidence: 99%
“…The ALDH2*2 allele is common in East Asian populations, in whom it has a well-established protective effect associated with about a 10-fold reduction in risk of alcoholism. 82 The protective effect is thought to be a direct consequence of the flushing reaction and associated nausea, drowsiness and headache that discourages drinking. In a recent meta-analysis, 83 researchers found clear evidence of a correlation between ALDH2 genotype and alcohol exposure (alcohol exposure being considered an environmental risk factor for cancer in much the same way that some psychiatrists view cannabis use as an environmental risk factor for schizophrenia).…”
Section: Genotype-environment Associations: Challenges In Identifyingmentioning
confidence: 99%
“…Since acetaldehyde is much more toxic than alcohol, it is associated with a larger number of the metabolic abnormalities in liver disease induced by alcohol. 9,10) Under normal conditions, acetaldehyde is rapidly converted to acetate by ADH, and therefore very low level of acetaldehyde should remain in the liver tissue or blood. ALDH also plays an important role in the elimination of acetaldehyde through oxidative reactions.…”
mentioning
confidence: 99%
“…Recently, in our review we suggested indirect mechanisms by which alcohol disrupts the EMPS . However, based on increasing evidences (Deitrich et al, 2006;Wick et al, 1998;Quertemont 2004;Buhler et al, 1983), a direct disruption might also be possible, especially, if we consider the possibility that receptors of neuromediators might have "alcohol pockets-receptors". It is reported that glycine and GABAA receptors may harbor specific pockets for alcohol .…”
Section: Pathways Of Alcohol's Action On the Error Monitoring And Promentioning
confidence: 99%
“…Indirect effect of alcohol on the processing capacity of the basal ganglia by affecting other brain areas connected to the basal ganglia; c. Direct effect on neuromediators that modulate the processing of information in the basal ganglia and/or associated brain pathways; d. Action of alcohol metabolites (acetaldehyde; acetate; protein, lipid, enzyme & DNA adducts of alcohol) on the processing of information in the basal ganglia and/or associated brain pathways. The brain might contain alcohol metabolizing enzymes such as ADH-1, ADH-2, ADH-3 (might play little or no role), CYP P4502E1 (Quertemont 2004;Buhler et al, 1983), although there might be a huge genetic variance. It important to note that injection of acetate into the brain causes significant decrease in motor function (Deitrich et al, 2006).…”
Section: Pathways Of Alcohol's Action On the Error Monitoring And Promentioning
confidence: 99%